Biochemical Modulation and Pathophysiology of Migraine. Issue 4 (December 2019) - Chan, Calvin; Wei, Diana Y.; Goadsby, Peter J.
Abstract : Background: Migraine is a common disabling neurological disorder where attacks have been recognized to consist of more than headache. The premonitory, headache, and postdromal phases are the various phases of the migraine cycle, where aura can occur before, during, or after the onset of pain. Migraine is also associated with photosensitivity and cranial autonomic symptoms, which includes lacrimation, conjunctival injection, periorbital edema, ptosis, nasal congestion, and rhinorrhoea. This review will present the current understanding of migraine pathophysiology and the relationship to the observed symptoms. Evidence Acquisition: The literature was reviewed with specific focus on clinical, neurophysiological, functional imaging, and preclinical studies in migraine including the studies on the role of calcitonin gene-related peptide (CGRP) and pituitary adenylate cyclase activating polypeptide (PACAP). Results: The phases of the migraine cycle have been delineated by several studies. The observations of clinical symptoms help develop hypotheses of the key structures involved and the biochemical and neuronal pathways through which the effects are mediated. Preclinical studies and functional imaging studies have provided evidence for the role of multiple cortical areas, the diencephalon, especially the hypothalamus, and certain brainstem nuclei in the modulation of nociceptive processing, symptoms of the premonitory phase, aura, and photophobia. CGRP and PACAP have been found to be involved in nociceptive modulation and through exploration of CGRP mechanisms, new successful treatments have been developed. Conclusions: Migraine is a complex neural disorder and is important to understand when seeing patients who present to neuro-ophthalmology, especially with the successful translation from preclinical and clinical research leading to successful advances in migraine management.